Etude et conception d’un diviseur de puissance Reconfigurable Gysel pour les applications mobiles - DJAIDJA, Tariq; Enca/ KENANE, El-Hadi (university of M'sila, 2022)
The world is witnessing an unparalleled revolution in the field of telecommunications, which has led to the emergence of many services in the form of the fourth-generation networks (LTE) and the 5G, Bluetooth networks, WLAN networks, etc., which in turn led to the emergence of the need to integrate many services into one device. In the same context, all active and passive microwave circuits must go along with the phenomenon of integration of services. Among these circuits, we mention the power divider, which is a main focus in this research. The latter (energy dividers) is one of the most important passive circuits that are used in many fields, such as medicine, surveillance, radar systems, and other applications. Among the most prominent power dividers we find the GYSEL splitter, which is classified among the types of power splitters that have a narrow bandwidth. In this work presented here, we designed several models of the GPD power divider using the CST Studio simulation program. We also conducted an analytical study of this divider using the ADS simulation program, in order to examine the effect of the geometric dimensions of the divider on its physical properties such as work frequency and bandwidth. After the analytical study, we designed a dual-band GPD splitter with two outputs which is dedicated for the application of WLAN 2.4 and 5.8 GHz.
Keywords: Gysel power divider, PIN diode, CST simulator, Reconfigurable power divider